Anti-TNF Exposure during Pregnancy in Crohn's Disease Patients - Silva, Elen Farinelli De Campos [UNESP]; Baima, Júlio Pinheiro [UNESP]; De Barros, Jaqueline Ribeiro [UNESP]; Renosto, Fernanda Lofiego [UNESP]; De Sibia, Carina De Fatima [UNESP]; Saad-Hossne, Rogério [UNESP]; Sassaki, Ligia Yukie [UNESP] (Karger Publishers, 2018)
Inflammatory bowel disease (IBD) affects young people of reproductive age. Therefore, a broad discussion is needed about the possible disease effects in pregnancy, as well as the risks of fetal exposure to the medications used, especially biological therapy. This study aimed to describe the management of 4 Crohn's disease patients who received anti-TNF therapy during pregnancy and present a literature review. We reported 4 cases composed of young women who became pregnant while receiving anti-TNF agents. The patients presented a satisfactory response to the clinical treatment and the pregnancies progressed without complications. We did not observe maternal or embryonic toxicity, or unfavorable outcomes. The available data point to inflammatory activity as the main risk factor for unfavorable gestational evolution to date, and showed anti-TNF therapy to be safe during pregnancy and breastfeeding. However, the benefits and risks must be discussed with the patient and management decisions should be taken on an individual basis.
Keywords: Anti-TNF therapy; Biological therapy; Crohn's disease; Inflammatory bowel disease; Pregnancy